2008
DOI: 10.1094/cchem-85-4-0507
|View full text |Cite
|
Sign up to set email alerts
|

Quality Trait Variation in Major Hard Red Spring Wheat Cultivars Released in North Dakota Since 1968

Abstract: Cereal Chem. 85(4):507-514Over the last 40 years, grain yield of hard red spring wheat (HRSW) (Triticum aestivum L.) has increased dramatically in North Dakota and neighboring regions. This yield increase has caused some concern that recent higher yielding cultivars might be released at the expense of quality performance. A two-year study was initiated in 2004 to examine the changes in quality performance of HRSW cultivars released by North Dakota State University (NDSU) over the past 40 years. The experiment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 10 publications
0
7
2
Order By: Relevance
“…Previously, Underdahl et al (2008b) reported no decline in quality over the period of 1968-2006; however, our results suggest that breadmaking quality has improved gradually since 1910. The presence or absence of a peak at a certain time point was used to create a binary set of data, which was used to construct the dendrogram.…”
Section: Figcontrasting
confidence: 77%
See 1 more Smart Citation
“…Previously, Underdahl et al (2008b) reported no decline in quality over the period of 1968-2006; however, our results suggest that breadmaking quality has improved gradually since 1910. The presence or absence of a peak at a certain time point was used to create a binary set of data, which was used to construct the dendrogram.…”
Section: Figcontrasting
confidence: 77%
“…Underdahl et al (2008b) analyzed the quality traits of 33 HRS wheat cultivars released after 1968, and the results showed no decline in end-use quality traits, such as mixing characteristics, and a significant improvement for crumb grain appearance. Underdahl et al (2008b) analyzed the quality traits of 33 HRS wheat cultivars released after 1968, and the results showed no decline in end-use quality traits, such as mixing characteristics, and a significant improvement for crumb grain appearance.…”
mentioning
confidence: 99%
“…Underdahl et al (2008b) did not detect statistically significant genetic gains for 14 of 15 quality traits that were studied in parallel to agronomic performance. The only quality trait that exhibited a significant positive response to year of cultivar registration was crumb color (Underdahl et al 2008b). The authors concluded that genetic gains in the agronomic performance of North Dakota spring wheat cultivars were not at the expense of end‐use quality, concurring with the results of Cox et al (1989).…”
Section: Resultsmentioning
confidence: 75%
“…In the current study, we detected statistically significant responses for time of cultivar registration on whole grain yellow pigment concentration, grain and flour protein concentration, SDS sedimentation volume, farinograph absorption, farinograph DDT, farinograph MTI, and loaf volume. Underdahl et al (2008b) did not detect statistically significant genetic gains for 14 of 15 quality traits that were studied in parallel to agronomic performance. The only quality trait that exhibited a significant positive response to year of cultivar registration was crumb color (Underdahl et al 2008b).…”
Section: Resultsmentioning
confidence: 75%
“…Improving wheat quality is a secondary goal. For instance, in a study conducted by Underdahl, Mergoum, Schatz, and Ransom (), it was determined that there was no improvement or decline in end‐use quality of wheat cultivars released in North Dakota between 1968 and 2008. However, improvements in yield and disease resistance were noted (Underdahl, Mergoum, Ransom, & Schatz, ).…”
Section: Introductionmentioning
confidence: 99%